Chorology and habitat characterization of Fritillaria caballeroi an endemic and threatened species in the Central System (Iberian Peninsula) - Amich, Francisco; Bernardos, Sonia (Lazaroa, 2013)
Fritillaria caballeroi F.M. Vázquez is an endemic threatened plant whose distribution is restricted to the mountains of the western sector of the Central System (Tormantos, Béjar, Francia and Estrela) and the Montes de León. Here we give a detailed description of its distribution in these territories and analyze the different physocoenoses in which it has become integrated.